Features of Local Bradyrhizobia Populations after Long-Term Period in the Soil without a Host Plant - Krutylo, D.V.; Nadkernychna, O.V.; Крутило, Д.В.; Надкернична, О.В. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
In previous years, the serological and genetic diversities of soybean nodule bacteria in agrocenoses of Ukraine have been researched. Less attention was paid to the study of their survival in the soil. Taking into account the natural heterogeneity of bacteria of the genus Bradyrhizobium, the aim of this work was to evaluate the diversity of bradyrhizobia in local populations of different soils after a long-term period without leguminous plants, to obtain new isolates of nodule bacteria and to study their properties. Methods. Microbiological (isolation of bradyrhizobia from the nodules of trap plants, study of the properties of strains), serological (study of the diversity of rhizobia in nodule populations, study of the serological affiliation of strains), vegetation and field experiments (study of plant infecting with bradyrhizobia). Results. Local populations of bradyrhizobia in sod-podzolic soil and leached chornozem were studied using trap plants of the genera Glycine, Vigna, and Lupinus. It was established that after a 7 to 8-year period without leguminous plants, active nodule bacteria remained in both types of soil, which nodulated cultivated and wild soybeans, cowpeas, mung beans, adzuki beans, and lupine. The main microsymbionts of plants of the genera Glycine and Vigna on different types of soil were soybean bradyrhizobia belonging to 6 serological groups: 46, M8, КВ11, 634b, HR, and B1. The representatives of 4 serogroups corresponded to the inoculant strains of Bradyrhizobium japonicum 46, M8, 634b, and КВ11, which were periodically used in the studied areas. In addition to B. japonicum, cowpea plants trapped microsymbionts of B. lupini serogroup 367a (4.2%) from the soil. Bradyrhizobia of serogroup B1 were detected both in nodules of cowpea (6.3%) and wild soybean (12.5%). 45.8% of lupine nodules were formed by bacteria B. lupini of serogroup 367a. The appearance in populations of representatives of serogroups HR and B1 along with a group of unidentified microsymbionts requires further research. Cultivation of trap plants of wild soybeans and various types of cowpea made it possible to identify saprophytic strain B. japonicum M8 (formed 25.0% to 83.4% of nodules) in the sod-podzolic soil, which did not infect the roots of cultivated soybeans. 70 isolates of bradyrhizobia were obtained from nodules of trap plants, which were preliminarily identified as B. japonicum, B. lupini, and Bradyrhizobium sp. Conclusions. The results confirm the importance of using different leguminous trap plants for a more complete characterization of the local rhizobial community. Cultivation of plants of the genera Glycine, Vigna, and Lupinus, capable of cross-infection, made it possible to detect bacteria B. japonicum (serogroups 46, M8, КВ11, 634b, HR), B. lupini (serogroup 367a), and Bradyrhizobium sp. (serogroup B1), which exist for a long-term period as saprophytes in sod-podzolic soil and leached chornozem. 70 isolates of bradyrhizobia were obtained, 35 of which were serologically related to the inoculant strains of B. japonicum introduced into the agrocenosis at the beginning of the research.